EPISTEMOLOGI NALAR BAYANI, BURHANI DAN IRFANI DALAM PENGEMBANGAN STUDI ISLAM - Muhammad Al Farabi; Zulkifli Tanjung; Riki Irawan (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2021)
In this era, we must become more clever and critical in analyzing things. Especially we as Muslims, we have to be smarter than others, and be responsible for what we get. For this reason, in this article the author will convey about several methods that can be used in seeking science, especially in the development of study Islam The methods of bayani, burhani and 'irfani are methods that we can use in seeking science, especially in Islamic studies. Thesethree methods have their respective functions, but in the study of Islamic educational philosophy, the bayani and  burhani methods are more often applied because this method uses the collapse of logic and can be proven to be true through natural laws, while the 'irfani method is rare because the science obtained from this method cannot be proven to be true  scientifically, but in the emotional state in feelings and hearts (dzauq) this method is most appropriate and feels most fitting and touching